1998
DOI: 10.1104/pp.116.1.319
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Physiological Responses to Water Deficit in Drought-Tolerant and Drought-Sensitive Lines of Sunflower1

Abstract: To investigate correlations between phenotypic adaptation to water limitation and drought-induced gene expression, we have studied a model system consisting of a drought-tolerant line (R1) and a drought-sensitive line (S1) of sunflowers (Helianthus annuus L.) subjected to progressive drought. R1 tolerance is characterized by the maintenance of shoot cellular turgor. Drought-induced genes (HaElip1, HaDhn1, and HaDhn2) were previously identified in the tolerant line. The accumulation of the corresponding transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(98 citation statements)
references
References 42 publications
6
89
1
2
Order By: Relevance
“…At the cellular level, water deficit may cause cellular damage or initiate adaptive responses (Cellier et al 1998). The products of stress-inducible genes can be classified into two groups (Bray 1997;Hasegawa et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…At the cellular level, water deficit may cause cellular damage or initiate adaptive responses (Cellier et al 1998). The products of stress-inducible genes can be classified into two groups (Bray 1997;Hasegawa et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest a clear relationship between dehydrin expression, in our case, PpinDhn3 and PpinDhn4, and drought stress (Fig. 6) using parameters such as water loss or Ψ nwpd , as described by other authors, e.g., Cellier et al (1998) and Volaire (2003).…”
Section: Discussionmentioning
confidence: 78%
“…Maintenance of favorable plant water relations is vital for the development of drought resistance in crop plants [27][28][29]. The water content in plant roots and leaves has been shown to be associated with drought tolerance in cultivated sunflower [30]. The results suggested that sunflower is sensitive to water deficiency during early vegetative stage, which could lead to severe loss in agricultural production of sunflower grown in drought conditions.…”
Section: Discussionmentioning
confidence: 99%